Towards a portable occam - Hill, David Timothy (Rhodes University, Faculty of Science, Department of Computer Science, 1988)
Occam is designed for concurrent programming on a network of transputers. AIlocation and partitioning of the program is specified within the source code, binding the program to a specific network. An altemative approach is proposed which completely separates the source code from hardware considerations. Static allocation is performed as a separate phase and should, ideally, be automatic but at present is manual. Complete hardware abstraction requires that non-local, shared communication be provided for, introducing an efficiency overhead which can be minimised by the allocation. The proposal was implemented on a network of IBM PCs, modelled on a transputer network, and implementation issues are discussed
Keywords: occam (Computer program language); Transputers; Parallel programming (Computer science)